The effect of spark exercise program on gross and fine motor skills of 6-8 year old boys with mental retardation (Revista de Investigaciones Universidad del Quindío, 2023)
It has been shown that children with mental disabilities have weaker basic motor skills than healthy children. The main aim of this study was to determine the effect of eight weeks of Spark training program on fine and gross motor skills of 6 to 8 year old male students with trainable mental disability. This research is of applied research and quasi-experimental research. By selecting the subjects from among the exceptional schools, 30 people were selected for the research. In the next stage, out of these 30 people, a pre-test was performed and 15 people in the Spark group and 15 people in the control group were randomly selected. The experimental group performed a training program selected by the Spark group for 24 sessions and 60 minutes in each session. During this time, the control group resumed its normal activities. The results showed that: Eight weeks of Spark training program has a significant effect on fine motor skills of 6 to 8 year old male students with trainable mental disability. The eight-week Spark training program has a significant effect on the gross motor skills of 6- to 8-year-old male students with trainable mental disabilities. Spark exercise program can have a significant positive effect on the gross and fine motor skills of mentally retarded children.
Keywords: Spark Training Program; Fine Motor Skills; Large; Trainable Mental Disability